Microbiological oxidation of high viscosity bitumen in soil; Eurasian Chemico-Technological Journal; Vol. 20, No. 2 - Filatov D. A.; Kopytov M. A.; Ovsyannikova V. S.; Elchaninova (El'chaninova) E. A. Elena Aleksandrovna (2018, 2018)
Title screen